Chapter Eagles and peacocks in tenth to twelfth-century Iberian art - Monteira, Inés (Taylor & Francis, 2024)
This book addresses the reception of Islamic visual culture by the northern Iberian kingdoms, by systematically comparing works of art from both sides and fleshing out their historical context. This study includes figurative and iconographic motifs, architectural forms, and even the spolia from constructions and Arabic inscriptions that were embedded in Christian buildings. The Islamic visual culture of al-Andalus was often transformed as it was recreated by Christian hands, bringing to the fore various nuances in the relationship between the two religious communities. Artistic transfer was conditioned by social coexistence between Christians and Muslims—both in the caliphate al-Andalus and in the northern realms—and military conflict. To approach the different ways in which Andalusi visual culture was received in the northern kingdoms, while embracing the vast diversity of case studies available, this book is divided into three thematic sections: Reinterpretation, Appropriation, and Artistic Transfers. This book will be of interest to scholars working in art history, visual culture, and medieval studies.